Valeria Manzano, The Age of Youth in Argentina. Culture, Politics, & Sexuality from Perón to Videla, Chapel Hill, The University of North Carolina Press, 2014, 329 páginas. - Caimari, Lila (2015)
Fil: Caimari, Lila. Universidad de San Andrés; Argentina.